Morphological tuning of membrane processing by temporal proton-metal cation substitution in perfluorosulfonic acid membranes. (1st December 2020) - Vetter, Kim-Marie; Reichbauer, Thomas; Martić, Nemanja; Reinisch, David; Hinrichsen, Olaf; Schmid, Günter
Abstract: We investigated how the exchange of the countercation in perfluorosulfonic acid (PFSA) membranes influences first their processability and secondly their electrochemical performance in water electrolysis. Cation-exchanged membranes were prepared (Li +, Na +, K +, Mg 2+, Zn 2+, Ca 2+, tetramethyl ammonium [TMA + ], tetrabutyl ammonium [TBA + ]) and their glass transition temperatures (Tg ) were assessed by dynamic mechanical analysis (DMA). A good correlation between the found Tg values and the processability of the membranes was found, imitating an industrial membrane electrode assembly (MEA) fabrication process. Li +, TBA + and Zn 2+ MEAs were electrochemically characterized in water electrolysis. Cyclic voltammetry (CV) polarization studies were performed to investigate initial effects of ion exchange based on the binding energies of the respective metal cation incorporated into the membrane. Impedance spectroscopy was used to measure membrane resistances during water electrolysis. Potentiostatic and galvanostatic experiments were employed to differentiate between initial and permanent effects, the latter arising from stable structural arrangements of the polymer side chains. In-situ potential-driven substitution (PDS) of the metal ions by protons was found to be quantitative for Li + . At 1.5 A/cm 2 the rate of PDS was 0.2 mmol/cm 2 per minute. However, morphological changes in the membrane remained, opening the possibility for morphological tuning of membrane fabrication by temporal proton-metal cation substitution.